1991
DOI: 10.1017/s0021859600077686
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of plant to soil concentrations of strontium-85 and its relation to properties of Greek soils

Abstract: SUMMARYPlant:soil ratios (CRs) of 85Sr concentration were studied in wheat, lucerne, lettuce, radish, string bean (Phaseolus vulgaris), and cucumber grown in pots in eight Greek soil types in a glasshouse pot experiment in 1989.The CRs of the crops and of the plant parts studied differed according to soil type. They ranged from 0·034–1·39 for wheat grains to 7·6–36·5 for cucumber stems and leaves. The CRs of the edible parts were much lower than those of the other plant material.The correlation between CRs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

1992
1992
1996
1996

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
0
8
1
Order By: Relevance
“…The disagreement of the results of our work with some of the results reported by Papanicolaou et al (1991Papanicolaou et al ( , 1992a must be attributed to the soils used. All soils used by Papanicolaou et al were inorganic.…”
Section: T H E Absolute Values Of Correlation Coefficientscontrasting
confidence: 93%
See 3 more Smart Citations
“…The disagreement of the results of our work with some of the results reported by Papanicolaou et al (1991Papanicolaou et al ( , 1992a must be attributed to the soils used. All soils used by Papanicolaou et al were inorganic.…”
Section: T H E Absolute Values Of Correlation Coefficientscontrasting
confidence: 93%
“…and to Ca in both extractable form or in the soil solution but not to pH neither to Ca and Ca + Mg, expressed as proportions of C.E.C., as Papanicolaou et al (1991Papanicolaou et al ( , 1992a were found for inorganic soils. and to Ca in both extractable form or in the soil solution but not to pH neither to Ca and Ca + Mg, expressed as proportions of C.E.C., as Papanicolaou et al (1991Papanicolaou et al ( , 1992a were found for inorganic soils.…”
Section: O N C L U S I O N Smentioning
confidence: 67%
See 2 more Smart Citations
“…S01 ' ' H f Jom different r e g l o n s °f . G [ eec <; (Papanicolaou et al 1991). The correlation between showing considerable differences in their phys.cal and CRs and soil properties was greatest for P H chemical properties were used in this experiment.…”
Section: Introduction Materials and Methodsmentioning
confidence: 95%